Risk taking as a distinctive intrapreneurial competence among university students - Cerro-Urcelay, itziar; Pinillos, María José; Blanco, María Rita (Journal of Management and Business Education, 2024)
The development of entrepreneurial and intrapreneurial initiatives is a significant factor for the economic and social progress of countries and is having a increasing interest in academic settings. The study was conducted on a sample of 337 Spanish university students from three fields of study (Education, Engineering, and Social Sciences). This work aims to measure intrapreneurial competencies in young Spanish university students, adapting the COIN_CR1 ©2017 scale for this purpose. A quantitative methodology was employed through the administration of self-reported surveys to the selected sample. The results indicate a proper behavior of the model in terms of the number of constituent dimensions and the competencies they encompass. Statistically significant differences were observed in the intrapreneurial competency dimension "Risk Taking", with higher scores among engineering students. This research seeks to contribute to a better understanding of the overall construct of intrapreneurship, intrapreneurial competencies, and the dimensions that form it.